Back to Basics: The Counsellor-Coach - Ponzo, Zander (Canadian Journal of Counselling and Psychotherapy, 2012)
This article portrays the counsellor as a life-skills coach who is able to assess human needs and to provide both developmental and remedial instruction in critical areas. Three salient fields for teaching basics are identified and six arenas in whichthe counsellor-coach may work are suggested. Counsellors are advised to ethically advertise their service and are urged to attend to their own personal development.